Pemanfaatan Data CHIRPS untuk Pemetaan Curah Hujan Per Kabupaten di Wilayah Jambi dengan Menggunakan ArcGIS - Umairoh, Putri Suci; Gusmira, Eva (Al-DYAS, 2025)
It was recorded that several areas in jambi region in the last 5 years from 2020 to 2024 have the potential to be affected by flooding, especially in densely populated urban areas and around the lowland, at least once a year there was flood with quite large water discharges that occurred during the rainy season.therefore, this research was carried out, where this research aims to explore information related to average rainfall which includes information on the distribution of rain, mapping rainfall part of district by utilizing rain datas that coincides in jambi area.another aim of this research is to learn more about how to map raw data using the ArcGIS application.this research uses monthly data sourced from CHIRPS (climate hazards center infra red precipitation with station data).this data is used as a solution for areas where rainfall data is rarely available and USGS: lansat 8 then the data will be processing using ArcGIS software.and then the data was summarized using Microsoft excel and from the result it can be seen that the distribution of rainfall in jambi is fairly even and is in the range of 1501-3000 mm at each district.